2012
DOI: 10.1152/ajpendo.00666.2011
|View full text |Cite
|
Sign up to set email alerts
|

Mammary gland serotonin regulates parathyroid hormone-related protein and other bone-related signals

Abstract: Hernandez LL, Gregerson KA, Horseman ND. Mammary gland serotonin regulates parathyroid hormone-related protein and other bonerelated signals. Am J Physiol Endocrinol Metab 302: E1009-E1015, 2012. First published February 7, 2012 doi:10.1152/ajpendo.00666.2011.-Breast cells drive bone demineralization during lactation and metastatic cancers. A shared mechanism among these physiological and pathological states is endocrine secretion of parathyroid hormone-related protein (PTHrP), which acts through osteoblasts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
96
1
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(109 citation statements)
references
References 54 publications
6
96
1
5
Order By: Relevance
“…This suggests that physiological responses to increased serotonin concentrations are different depending on the time point that is evaluated post-treatment. We have previously shown that PTHrP reached a maximal concentration in the circulation in response to 5-HTP in mice 3 h after treatment (Hernandez et al 2012). Moreover, serotonin has been shown to cause physiological changes to tight junctions in the mammary epithelium in a biphasic manner in the mammary gland (Pai & Horseman 2008).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This suggests that physiological responses to increased serotonin concentrations are different depending on the time point that is evaluated post-treatment. We have previously shown that PTHrP reached a maximal concentration in the circulation in response to 5-HTP in mice 3 h after treatment (Hernandez et al 2012). Moreover, serotonin has been shown to cause physiological changes to tight junctions in the mammary epithelium in a biphasic manner in the mammary gland (Pai & Horseman 2008).…”
Section: Discussionmentioning
confidence: 97%
“…Serotonin is synthesized by the mammary gland in several species (Matsuda et al 2004, Hernandez et al 2009, and it regulates several aspects of mammary gland function, including milk protein gene expression, the induction of parathyroid hormone-related protein (PTHrP) production, and mammary gland Ca pumps and transport (Matsuda et al 2004, Hernandez et al 2012, Laporta et al 2013a, 2014a. The concept that the mammary gland acts as an endocrine organ that secretes PTHrP into the circulation as a signal to target tissues to regulate Ca supply to the milk during lactation is well accepted in rodents and humans (Wysolmerski 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, serotonin was found to stimulate tumor growth when applied to invasive breast cancer cell lines, by promoting proliferation and epithelial-mesenchymal transition (Pai et al 2009). Moreover, serotonin was found to induce the transcription of parathyroid hormone-related protein and the metastasis-associated transcription factor Runx2/Cbfal via the serotonin receptor, 5-HT2 (Hernandez et al 2012). Hence, it is plausible that the activation of the serotonin receptor pathway in tumors arising during pregnancy may play a role in controlling the aggressive clinical behavior of these tumors.…”
Section: Discussionmentioning
confidence: 99%
“…In human breast cancer cells, 5-HT induced both parathyroid hormone-related peptide (PTHrP) and the metastasis-associated transcription factor Runx2/Cbfa1 (22). The mammary epithelium possesses a local serotonin signaling system which drives PTHrP expression during lactation and in breast cancer cells which may be a passage of breast communication to bone through serotonergic control of PTHrP (23).…”
Section: Introductionmentioning
confidence: 99%